Species diversity, elevational distribution and reproductive modes in an amphibian community at the Matang Range, Sarawak (Borneo) - Das, I.; Jankowski, A.; Makmor, M.I; Haas, A. (Hamburg, 2007)
We present an inventory of the amphibian fauna of the Matang Range, including Kubah National Park and the Matang Wildlife Centre areas of western Sarawak, East Malaysia (Borneo). A total of 55 species is reported, including 53 Anura and two Gymnophiona.